Novel synthesis and characterization of titanium superoxide and its application in organic oxidative processes - Reddy, R. Santhosh; Shaikh, Tanveer Mahamadali; Rawat, Varun; Karabal, Pratibha U.; Dewkar, Gajanan; Suryavanshi, Gurunath; Sudalai, Arumugam (Catalysis Surveys from Asia, 2010)
A novel, exceptionally stable titanium superoxide radical ion was prepared and its structure determined by FTIR, ESR, Raman spectroscopy, X-ray diffraction, thermogravimetric/differential thermal analysis and elemental analysis. This heterogeneous catalyst has been found to be effective for the selective oxidation of aromatic amines and phenols to the corresponding nitro aromatics and p-quinones, respectively. In addition, this non-toxic, inexpensive and reusable catalyst has also been used in aminobromination of olefins, which proceed to give the 1, 2-bromoaminated anti-Markovnikov product. A brief account of these results is summarized in this review.
Keywords: Amino Bromination; Anti-Markovnikov; heterogeneous catalyst; Oxidation; Titanium superoxide